Estudio de la estructura-función de la enzima isocitrato liasa (ICL) de Pseudomonas aeruginosa PAO1 - Díaz Pérez, Alma Laura (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The capacity of Pseudomonas aeruginosa to assimilate nutrients is essential for niche colonization and contributes to its pathogenicity. Isocitrate lyase (ICL) is the first enzyme of the glyoxylate cycle and redirects isocitrate from the tricarboxylic acid cycle to render glyoxylate and succinate. P. aeruginosa ICL (PaICL) is regarded as a virulence factor, due to its role in carbon assimilation during infection. The AceA/ICL protein family is integrated by subfamilies that share the catalytic domain I, which corresponds to triosephosphate isomerase barrel (TIM-barrel) domain. The carboxyl terminus of domain I is essential for Escherichia coli ICL (EcICL) of subfamily 1. PaICL, which belongs to subfamily 3, has domain II inserted at the periphery of domain I, which is believed to participate in enzyme oligomerization. In addition, PaICL has the α13-loop-α14 motif (extended motif), which protrudes from the enzyme core, being of unknown function. The aim of this study was to dilucidate the role of domain II, the extended motif and the carboxyl-terminal region in the function of the PaICL enzyme, and their involvement in the virulence of P. aeruginosa PAO1. Deletion of domain II and the extended motif resulted in inactivation and structural instability of the enzyme. The addition of a histidine tag at the C-terminus of PaICL resulted in a less efficient enzyme than the PaICL tagged at the N-terminus, but without affecting the acetate assimilation or virulence of the bacterium. The PaICL homotetramer is stabilized by ionic interactions and the C-terminus is critical for conformation of the PaICL quaternary structure.

La capacidad de Pseudomonas aeruginosa para asimilar nutrientes es esencial para la colonización de nichos ambientales y contribuye con su patogenicidad. La enzima isocitrato liasa (ICL) es la primera enzima del ciclo del glioxilato y desvía al isocitrato del ciclo de los ácidos tricarboxílicos hacia la producción de glioxilato y succinato. La ICL de P. aeruginosa (PaICL) se considera como un factor de virulencia, debido a su función en la asimilación de carbono durante la infección. La familia de proteínas AceA/ICL está integrada por subfamilias que comparten el dominio I catalítico, el cual corresponde al dominio del barril de la triosafosfato isomerasa (TIM-barrel). El extremo carboxilo del dominio I es esencial para la ICL de Escherichia coli (EcICL) de la subfamilia 1. La PaICL es parte de la subfamilia 3, tiene al dominio II insertado en la periferia del dominio I, el cual se propuso que participa en la oligomerización de la enzima. Adicionalmente, la PaICL contiene al motivo α13-loop-α14 (motivo extendido), el cual sobresale de la enzima y se desconoce su función. El propósito de este trabajo consistió en dilucidar la función del dominio II, del motivo extendido, y la región del extremo carboxilo en la función de la PaICL y su participación en la virulencia de P. aeruginosa PAO1. La deleción del dominio II y del motivo extendido resultó en la inactivación y en la inestabilidad estructural de la enzima. La adición de la etiqueta de histidinas en el extremo carboxilo de la PaICL originó una enzima menos eficiente que la PaICL etiquetada en el extremo amino; sin embargo, no se afectó la asimilación de acetato o la virulencia de la bacteria. El homotetrámero de la PaICL se estabilizó por interacciones iónicas y el extremo carboxilo fue crítico para la conformación de la estructura cuaternaria de la PaICL.
Instituto de Investigaciones Químico Biológicas. Doctorado en Ciencias en Biología Experimental
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16577; info:eu-repo/classification/cti/2; IIQB-D-2023-1137; Patogenicidad bacteriana; Isocitrato liasa; estructura proteica